0231 Occupational respirable cystalline silica exposure related to fev1 decline among normal or early abnormal ilo chest-radiographs of sandstone-workers; a six month follow up. (21st August 2017) - Chaiear, Naesinee; Trakultaweesuk, Peerawat; Boonsawat, Watchara
Abstract : Background: Respirable crystalline silica (RCS) exposure among cottage industrial results in rising silicosis case. Therefore medical surveillance remains crucial. Recently FEV1 decline has been established as a surveillance tool. Objective: To explore the relationship between occupational RCS exposure and FEV1 decline among sand-stone workers who had ILO chest radiographs profusion CAG ≤1/1. Material and method: This study was designed as a descriptive study. The participants were sand-stone workers and non-occupational RCS exposure (n=139) who had an ILO chest radiographs profusion CAG ≤1/1. FEV1 was measured using follow-up FVC manoeuvre spirometry testing. History of work, duration of exposure and other related issues were obtained through questionnaire interviews. Result: The majority of participants were female, non smokers and no previous respiratory diseases. Mean of FEV1 decline was found higher in the high RCS exposure group (118.6±137.7 ml) as compared to non-occupational RCS exposure group (median 45 ml, IQR 100 ml). When subgroup of non smokers considered, being classified into high exposure was found to have the highest FEV1 decline (99.3 ml ±129.9 ml.). In addition, the highest proportion of participants who had FEV1 decline >100 ml revealed in the high RCS exposure group (65.5%) followed by medium (43.8%) and low exposure group (19.6%) respectively . Conclusion: Intensity of RCS exposure strongly related to FEV1 decline. FEV1 decline more than 100 ml per year is appropriate to be used as a medical screening for RCS exposure and the effect could be found as early as six month exposure.